The Impact of Country of Origin Effect and Consumer Ethnocentrism on Purchase Intention of Foreign Brand Recreational Materials Used in Sports Activities: An Empirical Research - Murat Arslandere; Yusuf Er (Türk Spor ve Egzersiz Dergisi)
Enterprises operating in international markets in a globalizing world must take many factors into consideration in their activities. Country of origin effect and consumer ethnocentrism are among these factors. In this study, the goals were to determine (i) the effect of consumer ethnocentrism and the the country of origin effect on attitude towards the foreign brand and (ii) the effect of attitude towards the foreign brand on the purchase intention of foreign brand products. Foreign products were considered as recreational materials used in sports activities. A total of 335 participants (195 women (58%) and 140 men (42%), participated in the study. The data collected with the help of a structured questionnaire were statistically analyzed using SmartPLS 3.0 software. The results revealed that consumer ethnocentrism negatively influences attitude towards the foreign brand, country of origin effect positively influences attitude towards the foreign brand, and finally attitude towards the foreign brand has a strong and positive effect on the purchase intention of foreign brand products. Considering that Turkish consumers generally behave in favor of purchasing local products in textiles and clothing products, the fact that the country of origin effect has a positive effect on the foreign brand attitude of recreational materials used in sports activities has been the most striking point of the study.